PMMA-ZEOLITE 4A COMPOSITES NANOFIBERS AS FUNCTIONAL MATERIAL FOR ADSROPTION OF NI2+, CD2+ DAN ZN2+ IONS - Tri Suryandari, Ervin
Contamination of heavy metal ions into water bodies is a critical problesm. Eventhought some elements in trace amounts are essential for humans, plants and animals, but at certain concentrations it can be toxic to all living things. Especially the availability of heavy metal ions in the water can be derivated from automotive industries, batteries, tanning & metal coating prosesses. Therefore, it is necessary to create an effective strategy for removing heavy metal ions from waters, because at high concentrations it can undergo transformation into more toxic compounds. The adsorption is one of favorable methods for removal contaminant from water since it is high efficiency, easy handling, can be reused, inexpensive and provides alternatives of adsorbents, materials that have high selectivity and sensitivity.